If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 6 + 7x = -13 + 5 Reorder the terms: 6 + -6x + 7x = -13 + 5 Combine like terms: -6x + 7x = 1x 6 + 1x = -13 + 5 Combine like terms: -13 + 5 = -8 6 + 1x = -8 Solving 6 + 1x = -8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 1x = -8 + -6 Combine like terms: 6 + -6 = 0 0 + 1x = -8 + -6 1x = -8 + -6 Combine like terms: -8 + -6 = -14 1x = -14 Divide each side by '1'. x = -14 Simplifying x = -14
| 9=-2k+27 | | -7(w-4)+3w-27= | | 4=y-5 | | 2x^2=2x+3 | | 3x-(x-4)=2x | | 2(v-5)+7v+4= | | -4(5q+5)+4(q-4)= | | 3(4-c)-22=17c-5(2+4c) | | 6x^2+40x-14=0 | | 5w+3(9-2w)=18 | | 5(6x+8+-2x)=-10 | | -3x-2(2x+27)=-124 | | 12a+3+18-9a= | | 5x+6=2x-4 | | -5+5a-4-2a+3a= | | 3b-3-11b-9= | | 1x+6=2x-4 | | -7+g+1-6g= | | x+4*7=70 | | 18(x-2)-4(-9+3x)=-14 | | 5z-4=3(z+2) | | x-16=44 | | 3A-4=-13 | | 9x+8=3x-7 | | x^3+3x^2=18x | | -18(c-1)-18= | | 2x^2=6 | | 3x+5=4x-30 | | 1-4(u-1)= | | 7x-2x-10=25 | | 3x+5=2y-20 | | 18(x-2)-4(9+3x)=-14 |